1989
DOI: 10.1210/jcem-69-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Development of Spontaneous Hypothyroidism in Patients with Graves' Disease Treated with Antithyroidal Drugs: Clinical, Immunological, and Histological Findings in 26 Patients

Abstract: Graves' disease may result eventually in hypothyroidism in approximately 5-20% of patients. In a few such patients hypothyroidism was associated with TSH-blocking antibodies, but whether the frequency of TSH-blocking antibodies in such patients is as high as it is (21%) in patients with primary myxedema is not known. This study was undertaken to determine the presence of various immunoglobulins [TSH binding inhibitor immunoglobulins, thyroid-stimulating antibodies (TSAb), and TSH-blocking antibodies] in 26 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 0 publications
1
36
0
1
Order By: Relevance
“…Clinically evident ophthalmopathy occurs in about 50% of patients, in 75% of which the eye problems appear within a year before or after diagnosis of hyperthyroidism. Probably in relation to the activity of the underlying autoimmune process, Graves’ hyperthyroidism is characterized by an unpredictable course; in about 15% of cases, autoimmune hypothyroidism develops 10 to 15 years after presentation [5, 6]. Consistent with literature data, in a previous study we observed spontaneous evolution to hypothyroidism in almost 10% (10 of 105) of Graves’ patients [7].…”
Section: Introductionsupporting
confidence: 84%
“…Clinically evident ophthalmopathy occurs in about 50% of patients, in 75% of which the eye problems appear within a year before or after diagnosis of hyperthyroidism. Probably in relation to the activity of the underlying autoimmune process, Graves’ hyperthyroidism is characterized by an unpredictable course; in about 15% of cases, autoimmune hypothyroidism develops 10 to 15 years after presentation [5, 6]. Consistent with literature data, in a previous study we observed spontaneous evolution to hypothyroidism in almost 10% (10 of 105) of Graves’ patients [7].…”
Section: Introductionsupporting
confidence: 84%
“…The relatively sparse available information for this unusual group of patients is related to age, sex, and ethnicity (5,(29)(30)(31)(32)(33)(36)(37)(38)(47)(48)(49)(50)74). The majority of patients with TBAb/TSAb switches (or the reverse) are women, and they have the same age range as other patients with thyroid autoimmune disease (Table 4).…”
Section: Other Characteristics Of Patients Who ''Switch'' From Tbab Tmentioning
confidence: 99%
“…Hipotiroidi radyasyonun bir etkisidir ve lenfositik infiltrasyon ile tiroid dokusu harabiyetine bağlıdır 16 . Bizim çalışmamızda, 10 mCi ile %78.2 hastada RAI tedavisinden ortalama yaklaşık 5 ay sonra hormon replasmanı gerektiren hipotiroidi gelişirken, bu oran 15 mCi için ortalama 4. ayda %100'e ulaştı.…”
Section: Discussionunclassified